2019
DOI: 10.4103/ijstd.ijstd_20_17
|View full text |Cite
|
Sign up to set email alerts
|

Felt needs and expectations of adolescents regarding sexual and reproductive health from schools and health systems: A descriptive study

Abstract: Background: Much focus has been given to find ways to overcome the barriers that exist among adolescents in the utilization of sexual and reproductive health (SRH) services. This study attempts to explore the felt needs of adolescents regarding SRH education at schools and their expectations regarding SRH care from a health system. Methodology: A cross-sectional study was conducted among 400 1 st -year arts and science college students in Pudu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…School-age youth feel the need to have educational content on sexuality and reproductive health in schools and 33.5% of youth feel that the current related education is inadequate (Jennifer et al, 2012;Sreekumar et al, 2019). Health education sessions in schools are highly effective in increasing knowledge even though students have a tendency to forget information regarding some aspects that have been obtained over time (Jennifer, et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…School-age youth feel the need to have educational content on sexuality and reproductive health in schools and 33.5% of youth feel that the current related education is inadequate (Jennifer et al, 2012;Sreekumar et al, 2019). Health education sessions in schools are highly effective in increasing knowledge even though students have a tendency to forget information regarding some aspects that have been obtained over time (Jennifer, et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…One of the most critical ways of meeting the sexual and reproductive health needs of adolescents is through the provision of comprehensive, adolescent-friendly sexual and reproductive health services. Most adolescents are in need of various SRH services and studies in Nigeria and elsewhere have shown they at times self-medicate or go to unqualified providers for help, and may risk their health and lives as a result of unsafe practices [ 25 , 29 ]. The extent of preparedness of health facilities to provide ASRH services is critical to the utilization of these services by adolescents, and ultimately to the reduction and prevention of unintended teenage pregnancies and maternal mortality which are unacceptably high in Nigeria [ 30 ], as well as to the reduction of STI and HIV infections among adolescents [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most adolescents are in need of various SRH services and studies in Nigeria and India have shown they at times self-medicate or go to unquali ed providers for help and may risk their health and lives as a result of unsafe practices. 23,26 Many reasons have been given for this concerning state of affairs with the extent of preparedness of health facilities to offer ASRH services critical to the utilization of the services by adolescents, and ultimately to the reduction and prevention of unintended teenage pregnancies and maternal mortality which are unacceptably high in Nigeria, 27 as well as reduction of STI and HIV infections among adolescents. 19 The aim of the current research was to assess the provision of ASRH services in health facilities in Plateau State, Nigeria, in the light of the national policy which entails that ASRH be integrated into PHC facilities across the country.…”
Section: Discussionmentioning
confidence: 99%